Botanical formulations for the ecological management of Myzus persicae (Sulzer) and Aphis gossypii (Clover) (Hemiptera: Aphididae) and their side effects on parasitoids - Castresana, Jorge Eduardo; Puhl, Laura Elena (Universidad de Nariño, Colombia, 2021)
The peach aphid Myzus persicae (Sulzer) and cotton aphid Aphis gossypii (Clover) (Hemiptera: Aphididae) are considered to be key pests affecting greenhouse pepper crops in Argentina as a result of their frequent occurrence and the seriousness of the damage caused by their feeding behavior and the transmission of virus. The goal of this research was to determine the efficiency of botanical products to control aphids and their side effects on parasitoids in this crop. Thus, three biorational pest control formulations derived from essential oils (EO) and plant extracts (Es) were tested, namely (i) neem EO, cinnamon EO, clove EO, oregano EO and American marigold EO (formulation 1); (ii) garlic EO and cinnamon EO (formulation 2); (iii) garlic E and rue E (formulation 3); and a soy lecithin adjuvant (lecithin), and finally, a control (water spray method). For this research, a completely randomized design was replicated 3 times. These treatments were applied directly to the foliage by means of a backpack sprayer on a weekly basis until the end of this trial. Subsequently, the total number of healthy aphids and parasitized aphids (mummies) on every leaf was recorded in the field and the laboratory through repeated measures Analysis of Variance (ANOVA) and LSD Fisher method. The results showed that formulation 1 and formulation 3 recorded a lower number of aphids and mummies compared to the other treatments. This evidence would demonstrate that these formulations repel aphids and parasitoids without the lethal effects caused by the use of broad spectrum insecticides.